Developing Pancasila Character in Early Childhood: Strategies for Working Families - Toto Purbiyanto; Dasim Budimansyah; Encep Syarief Nurdin; Cecep Darmawan; Salman Rashid (Journal of Nonformal Education, 2025)
Background: The development of Pancasila character in early childhood is very important, especially in the context of working families who often face challenges in providing optimal character education. The character of Pancasila includes values such as justice, tolerance, and mutual cooperation, which need to be instilled from an early age to form a generation with integrity. Research Objectives: This research aims to explore the strategy of developing Pancasila character in early childhood in working families, as well as understand the experiences and challenges faced by parents in the process. Research Method: This study uses a qualitative phenomenological approach, which allows researchers to explore the subjective experiences of parents in developing Pancasila characters in their children. The data were collected through in-depth interviews with working parents, as well as observations of their interactions with children. Research Findings: The use of quality time with children, involving the family in character building, introducing children to religious and social activities, and the use of technology to learn Pancasila values, are all important aspects in shaping the character of Pancasila in children. This helps strengthen moral values, social concerns, and positive communication between parents and children, thereby helping children understand and apply Pancasila values better. Research Conclusion: This study concludes that the development of Pancasila character in early childhood in working families requires collaboration between parents, educational institutions, and the community. Greater support from the surrounding environment can help parents in implementing effective strategies. Research Novelty: This study provides new insights into how working families can contribute to the development of Pancasila character, as well as highlighting the importance of the role of the social environment in supporting the character education process at home.